Antimicrobial Activities of the Ethanol Extracts of Mirabilis jalapa L. and Euphorbia dendroide. - Muhammad Ikram; Gul Jan; Saim Dad; Nasrullah; Suliman; Hina Fazl (International Journal of Phytomedicine, 2013)
Antimicrobial activity was examined from two selected plants: Mirabilis jalap L. (stem, leaves and seeds) and Euphorbia dendroide (stem, leaves and root) different parts were screened against seven bacterial strains; three Gram positive (Staphlyococus aureus, Bacillus subtilis and Bacillus atropoeusand), four Gram negative (Escherichia coli, Pseudomonas aeruginosa, Salmonila typhi and Kleibsiella pneumonia) and one fungal strain Candida albican. Antibacterial activity was determined by the disc diffusion method; crude extracts were obtained by using ethanol as the extraction solvent. Two concentrations (6 mg/ml and 12 mg/ml) were used to check the antimicrobial activity of plant extracts. The result showed that Euphorbia dendroide different parts extracts were more active against gram negative bacteria and fungal strain then Mirabilis jalap L. while both plants showed good activity against gram positive bacteria. Azithromycin, Ciprofloxacin and Clotrimezole (50 µg/ml) were used as a standard drugs